2023
DOI: 10.1017/s104161022200103x
|View full text |Cite
|
Sign up to set email alerts
|

Reduction and prevention of agitation in persons with neurocognitive disorders: an international psychogeriatric association consensus algorithm

Abstract: Objectives To develop an agitation reduction and prevention algorithm is intended to guide implementation of the definition of agitation developed by the International Psychogeriatric Association (IPA) Design: Review of literature on treatment guidelines and recommended algorithms; algorithm development through reiterative integration of research information and expert opinion Setting: IPA Agitation Workgroup Participants: IPA panel of international ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 72 publications
0
12
0
Order By: Relevance
“…Agitation is a very troublesome behavioral problem in AD with major impacts, including costs and caregiver burden. 62,63 In a community-dwelling study involving older adults with a range of cognitive impairments, the prevalence of agitation ranged from 8.3% to 48.9%. 64 Agitation increases with dementia severity, and even higher rates (> 50%) are observed in nursing homes.…”
Section: Agitationmentioning
confidence: 99%
See 2 more Smart Citations
“…Agitation is a very troublesome behavioral problem in AD with major impacts, including costs and caregiver burden. 62,63 In a community-dwelling study involving older adults with a range of cognitive impairments, the prevalence of agitation ranged from 8.3% to 48.9%. 64 Agitation increases with dementia severity, and even higher rates (> 50%) are observed in nursing homes.…”
Section: Agitationmentioning
confidence: 99%
“…Dopamine-blocking agents can cause akathisia, a condition characterized by subjective and objective restlessness and typically seen in patients taking antipsychotics. 68 For nighttime disruptive behaviors, trazodone and orexin receptor antagonists (e.g., suvorexant, lemborexant) have been used [63]. Of note, a recent double-blind, placebocontrolled study (SYMBAD) found no effect of mirtazapine an atypical antidepressant with sedative properties at lower doses but activating in higheron AD-related agitation and potentially increased mortality associated with its use.…”
Section: Agitationmentioning
confidence: 99%
See 1 more Smart Citation
“…These interventions may include medication and nonpharmacological therapy. [8][9][10] Reminiscence therapy (RT) is one of the psychosocial approaches in which memories are used to protect and improve the mental health of older adults, improve their quality of life, and ensure the adaptation of older adults to the ageing process. 11 People's memories of the past help them maintain continuity in their internal psychological characteristics, social behaviour, and social conditions in the face of change.…”
Section: Introductionmentioning
confidence: 99%
“…However, several interventions can help manage the symptoms. These interventions may include medication and nonpharmacological therapy 8–10 …”
Section: Introductionmentioning
confidence: 99%